Nursing care for women in abortion situation: integrative review (Research, Society and Development, 2022)
Abortion is defined by the World Health Organization (WHO) as the expulsion of a lifeless fetus weighted less than 500g, which can be spontaneous or induced. It was taken as a goal here to identify in literature the nursing care provided to women in abortion situation. It is a Literature Integrative Review, accessed in August 2022, using academic papers published in the following bibliographic databases: Virtual Health Library (VHL), LILACS, MEDLINE, and BDENF. 81 research articles were found and added to 6 others from the present researchers’ personal archive, which after applying inclusion and exclusion criteria resulted in a sample of 11 articles selected according to the specifications of this research. It was observed that the care provided to these women still occurs in a discriminatory manner, opposing the guidelines of the Code of Ethics of the profession. Furthermore, abortion is a controversial and discriminatory issue for which humanized care by health professionals to women undergoing this process was perceived to be fundamental. It was also found that most professionals work according to their own set of principles, offering negligent assistance to these women in need of judgment-free care and support with dignity and respect for their rights.